2002
DOI: 10.1177/1538192702001002006
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Examination of Institutional Advancement Activities at Hispanic Serving Institutions

Abstract: Clearly, increased funding at the local, state, and federal levels would go a long way to ensure the future success of Hispanic Serving Institutions (HSIs) of higher education in the United States. Private funding and strong support from alumni groups are also a critical part of this funding mix. In addition, sophisticated and adequately funded marketing, public relations, and enrollment management efforts are needed. The funding of most HSIs is closely tied to the political process. Successful lobbying effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Early research centering HSIs did not address the idea of servingness, but it predicted the essential role HSIs would play in decreasing educational inequities, described their history as grounded in the Civil Rights Movement and connected to political advocacy and lobbying, and stressed their role in providing Latinx students with access to college (Laden, 2001(Laden, , 2004Olivas, 1982;Solórzano, 1995). More recent research has shown that HSIs are underresourced (de los Santos & Cuamea, 2010;Ortega, Nellum, Frye, Kamimura, & Vidal-Rodriguez, 2015), yet they lack the institutional capacity for advancement activities related to fundraising, government relations, and sponsored programs (Mulnix, Bowden, & López, 2002, 2004. With the growth in research centering HSIs, a debate has emerged in the literature about what it means to serve Latinx students within the context of HSIs.…”
Section: Conceptual Framework To Understand Hsis and Servingnessmentioning
confidence: 99%
“…Early research centering HSIs did not address the idea of servingness, but it predicted the essential role HSIs would play in decreasing educational inequities, described their history as grounded in the Civil Rights Movement and connected to political advocacy and lobbying, and stressed their role in providing Latinx students with access to college (Laden, 2001(Laden, , 2004Olivas, 1982;Solórzano, 1995). More recent research has shown that HSIs are underresourced (de los Santos & Cuamea, 2010;Ortega, Nellum, Frye, Kamimura, & Vidal-Rodriguez, 2015), yet they lack the institutional capacity for advancement activities related to fundraising, government relations, and sponsored programs (Mulnix, Bowden, & López, 2002, 2004. With the growth in research centering HSIs, a debate has emerged in the literature about what it means to serve Latinx students within the context of HSIs.…”
Section: Conceptual Framework To Understand Hsis and Servingnessmentioning
confidence: 99%
“…Two exceptions are recent work by Mulnix et al (2002) andDe Los Santos andDe Los Santos (2003). Mulnix et al (2002) brought attention to the documented disparities in institutional advancement activities which exist between HSIs and other universities around the country. According to the U.S. Department of Education (1998) the total revenues of HSIs are 42% less per full-time equivalent (FTE) student compared to other institutions.…”
Section: Hispanic Enrollmentmentioning
confidence: 99%
“…Hispanic-serving institutions (HSIs) are a federally recognized group of institutions whose enrollment is at least 25 percent Latino. Mulnix, Bowden, and López (2002) looked at giving to these institutions. Noting that funding is a perpetual issue for HSIs and that federal funding is a political issue, Mulnix, Bowden, and López (2002) believe that HSIs must look toward private funding and support from alumni.…”
Section: Philanthropy To Hispanic Serving Institutionsmentioning
confidence: 99%
“…Mulnix, Bowden, and López (2002) looked at giving to these institutions. Noting that funding is a perpetual issue for HSIs and that federal funding is a political issue, Mulnix, Bowden, and López (2002) believe that HSIs must look toward private funding and support from alumni. They found that HSIs in general are very new to institutional advancement and that sophisticated, well-funded marketing, public relations, and enrollment management are necessary.…”
Section: Philanthropy To Hispanic Serving Institutionsmentioning
confidence: 99%